2014
DOI: 10.1242/jcs.149633
|View full text |Cite
|
Sign up to set email alerts
|

Podosome-regulating kinesin KIF1C translocates to the cell periphery in a CLASP-dependent manner

Abstract: The kinesin KIF1C is known to regulate podosomes, actin-rich adhesion structures, which remodel the extracellular matrix during physiological processes. Here we show that KIF1C is a player in the podosome-inducing signaling cascade. Upon induction of podosome formation by protein kinase C, KIF1C translocation to the cell periphery intensifies and KIF1C accumulates in the proximity of peripheral microtubules enriched with plus tip-associated proteins CLASPs and around podosomes. Importantly, without CLASPs, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 59 publications
5
66
0
Order By: Relevance
“…Multiple microtubule-associated factors, including kinesins KIF1C, KIF5B, KIF3A/B and KIF9, +TIPs EB1 and CLASP1, as well as deacetylase HDAC6, have been linked to the formation of podosomes (Bhuwania et al, 2014;Biosse et al, 2014;Cornfine et al, 2011;Destaing et al, 2005;Efimova et al, 2014;Maridonneau-Parini, 2014;Wiesner et al, 2010;Zhu et al, 2016). Podosomes, which are characterized by specialized organization of actin and adhesion molecules and the ability to degrade ECM, thus appear to depend on different aspects of microtubule regulation and microtubule-based transport for their function.…”
Section: Microtubule-associated Proteins In 3d Cell Migrationspecificmentioning
confidence: 99%
“…Multiple microtubule-associated factors, including kinesins KIF1C, KIF5B, KIF3A/B and KIF9, +TIPs EB1 and CLASP1, as well as deacetylase HDAC6, have been linked to the formation of podosomes (Bhuwania et al, 2014;Biosse et al, 2014;Cornfine et al, 2011;Destaing et al, 2005;Efimova et al, 2014;Maridonneau-Parini, 2014;Wiesner et al, 2010;Zhu et al, 2016). Podosomes, which are characterized by specialized organization of actin and adhesion molecules and the ability to degrade ECM, thus appear to depend on different aspects of microtubule regulation and microtubule-based transport for their function.…”
Section: Microtubule-associated Proteins In 3d Cell Migrationspecificmentioning
confidence: 99%
“…It is thought that kinesin 3 motors cooperate with dynein for bidirectional motility, so whether PTL 1 affects Unc 104 directly or negatively regulates dynein to cause the observed phenotype remains to be elucidated. The microtubule plus end tracking protein CLASP is required to stimulate the trafficking of KIF1C [119]. KIF1C has also been described to move with growing microtubule plus ends in cells [120].…”
Section: Specificity For a Subset Of Microtubule Tracksmentioning
confidence: 99%
“…This could be either due to the preference for unmodified (i.e. freshly assem bled) microtubules [108], or due to its fast transport speed and thus ability to catch up with the growing microtubule end [51], or due to its interaction with CLASP [119].…”
Section: Specificity For a Subset Of Microtubule Tracksmentioning
confidence: 99%
“…The CLASPs (CLASP1 and CLASP2), discovered in 2001 as binding partners for the CAP-Gly domain-containing linker proteins 1 and 2 (CLIP1/CLIP-170 and CLIP2/CLIP-115), were initially found to bind and stabilize the growing, distal ends of microtubules, independently of the CLIPs (17). Subsequent studies revealed that CLASPs localize wherever microtubules are needed, kinetochores in the nucleus for mitosis (18)(19)(20)(21)(22)(23), the cell cortex (24-27), the leading edge lamella and lamellipodium of motile cells (28)(29)(30)(31), the Golgi (17,(32)(33)(34)(35)(36)(37)(38), axons (39, 40), the developing apical membrane surface during lumen formation within endothelial cells (41), adherens junctions at cell-cell contacts (42, 43), the neuromuscular junction (44)(45)(46), podosomes (47), and focal adhesions (48). Within each of these molecular systems, the dynamic instability of microtubules undergo differential regulation by proteins specific to each of the biological processes (49)(50)(51)(52)(53)(54)(55).…”
Section: Introductionmentioning
confidence: 99%